Boundary element method simulation of 3D heat diffusion in defective layered media for IRT building applications. (August 2017) - Serra, C.; Tadeu, A.; Simões, N.
Abstract: This paper presents a numerical model to simulate heat transfer by conduction in defective layered media, looking to contribute to the interpretation of thermographic results obtained in active Infrared Thermography (IRT) tests performed on building elements. The proposed model is developed to simulate 3D heat diffusion in a multilayered system containing a 3D thin defect (considered to be a null thickness inclusion). The proposed model uses the frequency domain Boundary Element Method (BEM) formulation written in terms of normal derivative integral equation formulation, referred to here as TBEM, in order to handle the null thickness of the defect. 3D Green's functions for multilayered media are used to avoid the discretization of the interfaces between layers. These 3D Green's functions are expressed as Bessel integrals and written as the sum of source terms and terms which are defined by imposing the required boundary conditions at each interface. When using this procedure, only the defect's surface is discretized. The proposed solution is verified against a previously developed 3D TBEM formulation for unbounded media using a mirror image source technique. To illustrate the applicability of the proposed methodology in active IRT, time-domain and phase contrast results are simulated and presented.